Quantum Quadratic operators and processes - Mukhamedov, Farrukh; Ganikhodjaev, Nasir (Springer, 2015)
Covering both classical and quantum approaches, this book presents the most recent developments in the theory of quadratic stochastic operators and their Markov and related processes. The asymptotic behavior of dynamical systems generated by classical and quantum quadratic operators is investigated and various properties of quantum quadratic operators are studied, providing an insight into the construction of quantum channels